Structural and non-structural ways of managing floods with respect to the climate change situation - Salleh, Md Noor; Hakim, Nur Wajihah; Al-Mamun, Abdullah; Ayob, Mohd Fairullazi; Sekaran, Thayalam; Ismail, Mohd Azmi; Mat Amin, Mohd Zaki (National Water Research Institute of Malaysia, 2021)
Flooding is historically a major environmental problem in many parts of the world. Malaysia is one of those countries that frequently experiences flash and regional flooding due to geographical location, topography, climate and the improper development activities. Appropriate flood management measures need to be put in place to reduce negative flood impacts. Such measures can be categorized as structural measures and non-structural measures. Numerous structural and non-structural flood management already being introduced for example dams, levees, floodways, flood wall, river improvement, education, public awareness, flood warnings and many more. Such measures are intended to reduce the frequency and amount of damages due to flooding. Climate change and global warming are aggravating the flood impacts on the society and environment. As such, this paper is intended to review the flood management techniques already being implemented around the world and their suitability with respect to the climate change that already has happened and might happen in the future. This paper discusses the past, present and future perspectives of managing floods through structural and non-structural techniques. The advantages and disadvantages of such methods on the people, community, economy and the environment under the climate change situation are also attempted to be evaluated.